The Impact of Human Capital Readiness on Business Performance : The Mediating Role of Innovation Capability: Pengaruh Ketersediaan Human Capital pada Kinerja Bisnis: Peran Mediator Kemampuan Inovasi - Linda Sutanto; Bambang Tjahjadi; Fiona Niska Dinda Nadia (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the role of innovation capabilities in mediating the link between human capital readiness and business performance. This study's essential contribution is empirically examining the resource-based theory using a structural equation model. This study is a quantitative investigation at the explanatory level that employs structural equation modelling. In Indonesia, 258 owners or managers from MSME’s. The following are the findings: Human capital readiness impacts business performance. Second, innovation capability impact on business performance. Third, innovation capability mediate the relationship between human capital readiness and business performance. This study concludes the strategic roles of innovation capability in Indonesian MSMEs.